Seven new species of Urocleidoides (Monogenea: Dactylogyridae) from Brazilian fishes supported by morphological and molecular data - Zago, Aline Cristina [UNESP]; Yamada, Fábio Hideki; de Oliveira Fadel Yamada, Priscilla [UNESP]; Franceschini, Lidiane [UNESP]; Bongiovani, Marcela Fontes [UNESP]; da Silva, Reinaldo José [UNESP] (Springer Nature, 2020)
Seven new species of Urocleidoides from the gills and skin of nine Neotropical fish hosts (Anostomidae, Parodontidae, and Gymnotidae) are described: Urocleidoides digitabulum n. sp. on Leporinus friderici, Leporinus octofasciatus, and Megaleporinus elongatus (Anostomidae); Urocleidoides solarivaginatus n. sp. on L. friderici, L. octofasciatus, and Leporinus striatus (Anostomidae); Urocleidoides falxus n. sp. and Urocleidoides sapucaiensis n. sp. on M. elongatus; Urocleidoides tenuis n. sp. on Apareiodon piracicabae and Apareiodon affinis (Parodontidae); Urocleidoides sinus n. sp. on L. striatus, Schizodon nasutus, and Schizodon intermedius (Anostomidae); and Urocleidoides uncinus n. sp. on Gymnotus sylvius (Gymnotidae). Urocleidoides paradoxus was also found in this study on L. friderici and included in the phylogenetic analysis. Molecular data (partial 28S rDNA and mitochondrial cytochrome oxidase subunit I) were obtained for U. digitabulum n. sp., U. tenuis n. sp., U. sinus n. sp., and U. uncinus n. sp. The identification of Urocleidoides is amended herein to include all taxonomic modifications observed in this genus over time and add new characteristics observed in the species in the present study. Phylogenetic analysis revealed Urocleidoides digitabulum n. sp. and Urocleidoides sinus n. sp. (parasites of anostomids) closely related in the tree topologies. Furthermore, the new species described herein parasitized phylogenetically distant host species (Characiformes and Gymnotiformes), suggesting the effect of the dynamic process of ecological fitting.
Keywords: 28S rDNA fragments; Anostomidae; COI mtDNA; Gymnotidae; Neotropical region; Parodontidae